Vernal keratoconjunctivitis and keratoconus. Issue 5 (October 2021) - Wajnsztajn, Denise; Solomon, Abraham
Abstract : Purpose of review: Vernal keratoconjunctivitis (VKC) is a severe allergic inflammatory disease affecting the conjunctiva in children and young adults. Keratoconus (KC) is a progressive corneal disease characterized by thinning of the corneal stroma, increased and asymmetric corneal curvature, with a potential for significant visual deterioration and is one of the most common corneal complications of VKC. We aimed to review the association of these two diseases, with focus on the mechanisms, prevalence, natural history and treatment strategies of KC associated with VKC. Recent findings: KC is a common complication of VKC. KC prevalence can be as high as 26.8% among VKC patients, whereas abnormal corneal topography may appear in up to 71% of them. It is more severe and progresses faster in the setting of VKC ( P  < 0.05), with remarkable visual deterioration and with an increased need for keratoplasty. Crosslinking treatment and corneal transplantation appear to be as effective for KC patients with VKC as compared to the patients without VKC. However, postoperative complications are higher in patients with VKC and demand close monitoring, tight control of local inflammation and prompt awareness with consequent restrain of eye rubbing. Summary: Patients with VKC should be closely monitored for KC. Prompt recognition of VKC and KC allows tight control of KC pathogenesis mechanisms, timely management of KC progression and preservation of vision and quality of life of young patients.